Il Montalbano nel Medioevo Storia e archeologia di un territorio di frontiera - Somigli, Lapo (Premio Ricerca «Città di Firenze», 2021)
This book analyses the dynamics of settlement and power in medieval Montalbano, for centuries a frontier area contested by competing powers. The architectural evidence, particularly religious, is investigated archaeologically as manifestations of power. Starting from the study of the technical knowledge of medieval master masons, the cultural, economic and political dynamics of an area to which the frontier gave centrality and supra-regional exchanges, especially during the 11th century, have been reconstructed. It is no coincidence that this centrality diminished from the following century when the growing influence of Pistoia's municipality was matched by material standardisation. The contribution given to research and data analysis by the use, also experimental, of computer tools (3D, GIS) is also fundamental.